Pola Asuh Gizi Seimbang Pada Left-Behind Children di Kabupaten Banyuwangi - Adhi Cahya Fahadayna; Mulya Agustina; Elita Indah Mawarni (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Stunting is a significant nutritional issue that hinders children's ability to reach their full growth potential. In Indonesia, it remains a national priority, with Muncar District in Banyuwangi Regency having the highest prevalence of stunting, a situation worsened by the COVID-19 pandemic. The primary contributing factors include a widespread lack of awareness of proper nutrition and a misalignment between community needs and the intervention strategies implemented by the Banyuwangi Regency government. Additionally, the Banyuwangi Regency is one of Indonesia's largest sources of migrant workers, exacerbating stunting vulnerabilities among left-behind children due to parental absence and limited knowledge of nutrition and parenting. To address this gap, the initiative aimed to enhance migrant parents' awareness and understanding of proper nutritional practices, thereby supporting their children's growth and development. This community service program was conducted in collaboration with the Banyuwangi Regency Manpower, Transmigration and Industry Service, Banyuwangi College of Health Sciences, and Muncar District Government. It comprised three core sessions: education on Clean and Healthy Lifestyle Behavior (CHLB); Nutritious, Diverse, Balanced, and Safe (B2SA) food; and a workshop on utilizing local ingredients to create stunting-preventive meals. The program yielded significant outcomes, with 20 parents participating and demonstrating an improved understanding of CHLB and B2SA foods, along with practical skills in preparing nutritious meals using local ingredients. This initiative serves as a foundational strategy for reducing stunting in the Muncar District and contributes to Indonesia’s broader efforts to mitigate this nutritional issue.